Stock Status Assessments for 12 Exploited Fishery Species in the Tsushima Warm Current Region, Southwest Japan and East China, Using the CMSY and BSM Methods - Wang, Yuanchao; Liang, Cui; Wang, Yibang; Xian, Weiwei; Palomares, Maria Lourdes (Frontiers in Marine Science, 2020)
This contribution presented stock assessments for 10 fish and 2 squid populations exploited by Chinese, South Korean, and Japanese fishing fleets in the Tsushima Warm Current region, i.e., Southwest Japan and East China. The methods used were a Monte Carlo method (CMSY) and a Bayesian state-space implementation of the Schaefer model (BSM), based on published time series of catch and abundance data (SSB and CPUE). Results showed that 2 fish stocks, Japanese jack mackerel (Trachurus japonicus) and yellowback sea-bream (Dentex hypselosomus), had a healthy status, while daggertooth pike conger (Muraenesox cinereus) appeared to have collapsed. The other 9 stocks showed varying degrees of overfishing. The cooperation of several countries would be required to recover the fishery resources in the Tsushima Warm Current region.